Michka - Colmont, Marie, 1895-1938.; Franquin, Girard (Madrid : Everest, 1993)
A stuffed bear decides to leave his well-off master to live with a poor child who has no other toys.
"A partir de 6 anos"--back cover.
Keywords: Children's stories; Teddy bears; Stuffed animals (Toys)